RESTORATIVE JUSTICE FOR CONVICTIONS WITH MARIJUANA NARCOTICS: RESTORATIVE JUSTICE BAGI TERPIDANA NARKOTIKA JENIS GANJA - Hidayat, Riyan (LPPM UPMI, 2023)
Restorative justice is an alternative settlement of criminal cases in which the mechanism of criminal justice procedures focuses on punishment which is converted into a dialogue and mediation process involving perpetrators, victims, families and other related parties to jointly create an agreement on the settlement of criminal cases fair and balanced for victims and perpetrators by prioritizing restoration to its original state, and restoring good relations in society. The Supreme Court considers that it is necessary to apply Restorative Justice for several cases, one of which is the narcotics case which must be carried out by all district court judges and heads of high courts through the Decree of the Director General of the General Judiciary Agency of the Supreme Court of the Republic of Indonesia Number 1691/DJU/SK/PS.00 /12/2020 concerning the Enforcement of Guidelines for the Implementation of Restorative Justice in the General Courts (abbreviated as